Rethinking the Social Foundations of Environmental Politics: Evidence from Bali, Indonesia - Kadek Dwita Apriani; Gde Dwitya Arief Metera (Universitas Warmadewa, 2026)
What constitutes the social foundation of environmental politics in the Global South? Existing scholarship advances two influential accounts. One, derived largely from research in advanced industrial democracies, characterizes environmental concern as a post-materialist phenomenon concentrated among affluent and highly educated middle classes. The other, grounded in case studies from developing contexts, emphasizes precarious movements among economically vulnerable communities. Whether these frameworks adequately capture environmental dynamics in middle-income societies, however, remains an open question. This article examines the case of Bali, Indonesia, a province that has experienced intensifying environmental pressures alongside growing public engagement with ecological issues. Drawing on an original representative survey of 1,893 respondents across nine districts (multistage random sampling; margin of error 2.8 per cent at 95 per cent confidence), the study analyses the distribution of pro-environmental behavior across socio-economic and educational strata. The findings indicate that pro-environmental behavior in Bali is not confined to either affluent, highly educated constituencies or economically marginal groups. Rather, environmentally aligned practices are observable across social strata. While differences in degree remain, the overall pattern suggests a more socially dispersed foundation than either the post-materialist or the environmentalism of the poor framework would predict. The article contributes to comparative debates by inviting a reconsideration of the North–South binary as an organizing framework for the study of environmental politics.